Access to Credit Information Promotes Market Entries of European Banks - Nicola Jentzsch; Caterina Giannetti; Giancarlo Spagnolo (Weekly Report, 2010)
When granting credit, banks depend on reliable information about the creditworthiness and risk structure of potential borrowers. This information is typically gathered by national credit bureaus. Nationally established banks depend on information from credit bureaus more than ever, particularly when entering a foreign market. This DIW study (which is partially based upon research by the same authors for the European Credit Research Institute and data collected by the institute) investigates whether the existence of credit bureaus influences European bank competition and concludes that they facilitate market entry for foreign banks. In turn, the absence of credit bureaus can create significant disadvantages in competition. In this case, a market entry is then primarily possible via the purchase of an incumbent bank, because the entering institution has essentially no other opportunity to access debtor data. This study also shows that provision of data within the EU is not harmonized overall.
Keywords: F37; G21; G34; L13; O16; 330; Credit registers; Foreign entry asymmetric information